Advances in Jellyfish Sting Mechanisms and Treatment Strategies - Bingbing Li; Yueyue Li; Zhiwen Qiu; Chuantao Zhang; Yue Li; Wei Li; Jishun Yang (Marine Drugs, 2025)
Jellyfish stings, as one of the most prevalent forms of marine injury, have increasingly become a subject of concern. Despite their simple morphology and structure, jellyfish possess a complex venom composition that can inflict varying degrees of damage on multiple human physiological systems. Consequently, the clinical symptoms associated with jellyfish stings are highly intricate. Although antivenoms have been developed for certain jellyfish species (e.g., C. fleckeri), specific antivenoms targeting the mechanisms of most jellyfish venoms remain understudied. To effectively prevent, treat, and cure jellyfish stings, we adhere to the principle of knowing their nature and their reasons. It is essential to investigate the emission mechanism of jellyfish nematocysts and the composition of their venom. Understanding these factors is crucial for the development of targeted treatment strategies. This review delves into the venom emission mechanism of jellyfish stinging cells, the symptoms resulting from jellyfish stings, and the comprehensive treatment strategies post-sting. It offers a scientific reference for comprehending jellyfish stings and establishes a theoretical foundation for subsequent research endeavors.